Modulation of adipogenesis-related gene expression by ethanol extracts of Detam 1 soybean and Jati belanda leaf in 3T3-L1 cells - Meilinah Hidayat; Sijani Prahastuti; Nurul Fauziah; Maesaroh Maesaroh; Balqis Balqis; Wahyu Widowati (Bangladesh Pharmacological Society, 2016)
In this study, we evaluated the effects of ethanol extracts of Detam 1 soybean, Jati belanda leaf, and the combination toward expression of peroxisome proliferator-activated receptor gamma (PPAR?), CCAAT/enhancer-binding protein alpha (C/EBP?), and stearoyl-CoA desaturase 1 (SCD1) genes in 3T3-L1 cells as anti-adipogenesis and anti-obesity. The differentiation of 3T3-L1 cells into adipocyte was conducted using induction medium consist of Dulbecco's Modified Eagle's Medium, 3-isobutyl-1-methylxanthine, insulin, dexamethasone, and fetal bovine serum. The expression of PPAR?, C/EBP?, and SCD1 gene was measured using real-time quantitative polymerase chain reaction (qPCR). Ethanol extract of Jati belanda at a concentration of 50 ?g/mL was most effective to reduce PPAR?, C/EBP?, and SCD1 gene expression in 3T3-L1 cells. Ethanol extract of Detam 1 soybean failed to reduce PPAR? gene expression, whilst in the concentration of 50 ?g/mL it was able to significantly reduce the C/EBP? and SCD1 gene expression. Both ethanol extracts of Detam 1 soybean and Jati belanda have potential as anti-adipogenesis and anti-obesity by suppressing adipogenesis-related gene expression, particularly C/EBP? and SCD1. Video Clip of Methodology: Maintaining 3T3-L1 cell culture: 5 min 15 sec   Full Screen   Alternate